Mind mapping with proofblocks effects on student geometric level of thinking and self-efficacy - Velasco, Quinn Madiline R. (College of Education, University of the Philippines Diliman, 2013)
This study investigated the effects of Mind mapping with proofblocks approach on student geometric level of thinking and mathematics self-efficacy. It also examined the relationship between student geometric level of thinking and mathematics self-efficacy as well as the interaction between visual-spatial intelligence and teaching approach in terms of geometric level of thinking. The research utilized a quasi-experimental pretest-posttest control group design. Two heterogeneous third year sections from different public high schools were randomly assigned to experimental and control group. Experimental group was exposed to Mind mapping with proofblocks approach while control group was taught using conventional approach. This study was conducted for four weeks during second quarter of Academic Year 2012- 2013 and the researcher handled both classes. The significant level was set at .05 for all statistical tests used. Pretests results showed that the 33 students from experimental group and 41 students from control group were initially comparable in terms of geometric level of thinking, mathematics self-efficacy, and visual spatial intelligence. After groups were subjected to their respective teaching approach, posttests results revealed that experimental group had significantly higher geometric level of thinking and mathematics self-efficacy than control group. Analysis on the effects of visual-spatial intelligence on the treatment implied that regardless of student level of visual-spatial intelligence, treatment was not influenced. Results also showed a positive significant correlation between geometric level of thinking and mathematics self-efficacy. Based on these results, it can be concluded that the use of mind mapping with proofblocks in teaching and learning geometry results to a higher student geometric level of thinking and mathematics self-efficacy.